Longitudinal characterization of determinants associated with obesogenic growth patterns in early childhood. (10th September 2022) - Michael, Navin; Gupta, Varsha; Fogel, Anna; Huang, Jonathan; Chen, Li; Sadananthan, Suresh Anand; Ong, Yi Ying; Aris, Izzuddin M; Pang, Wei Wei; Yuan, Wen Lun; Loy, See Ling; Thway Tint, Mya; et al.
Abstract: Background: Longitudinal assessment of the determinants of obesogenic growth trajectories in childhood can suggest appropriate developmental windows for intervention. Methods: Latent class growth mixture modelling was used to identify body mass index (BMI) z-score trajectories from birth to age 6 years in 994 children from a prospective mother–offspring cohort (Chinese, Indian and Malay ethnicities) based in Singapore. We evaluated the early-life determinants of the trajectories as well as their associations with cardiometabolic risk markers at age 6 years. Results: Five BMI z-score trajectory patterns were identified, three within the healthy weight range, alongside early-acceleration and late-acceleration obesogenic trajectories. The early-acceleration pattern was characterized by elevated fetal abdominal circumference growth velocity, BMI acceleration immediately after birth and crossing of the obesity threshold by age 2 years. The late-acceleration pattern had normal fetal growth and BMI acceleration after infancy, and approached the obesity threshold by age 6 years. Abdominal fat, liver fat, insulin resistance and odds of pre-hypertension/hypertension were elevated in both groups. Indian ethnicity, high pre-pregnancy BMI, high polygenic risk scores for obesity and shorter breastfeeding duration were common risk factors for both groups. Malay ethnicity and low maternal educational attainment were uniquely associated with early BMI acceleration, whereas nulliparity and obesogenic eating behaviours in early childhood were uniquely associated with late BMI acceleration. Conclusion: BMI acceleration starting immediately after birth or after infancy were both linked to early cardiometabolic alterations. The determinants of these trajectories may be useful for developing early risk stratification and intervention approaches to counteract metabolic adversities linked to childhood obesity.